Health education website on home care for newborns: construction, validation, and evaluation - Iasmym Alves de Andrade Soares; Fernanda Garcia Bezerra Góes; Aline Cerqueira Santos Santana da Silva; Fernanda Maria Vieira Pereira-Ávila; Gabrielle Beltrão de Oliveira; Maria da Anunciação Silva (Universidade de São Paulo, 2024)
Objective: to build, validate, and evaluate an educational health website on home care for newborns for use by pregnant women, postpartum women, and family members. Method: methodological study developed according to the Analyze, Design, Develop, Implement, and Evaluate model. After construction, the website was validated by 20 experts and evaluated by 20 individuals from the target audience, and the data wasanalyzed according to the Concordance Index with a cut-off point equal to or greater than 0.7 (70%). Results: in the validation, the Concordance Index for all the items was higher than 0.7 (70%), with a variation between 0.75 (75%) and 1 (100%), reaching an overall average value of 0.91 (91%). In the evaluation, all the items got top marks, with anoverall average value of 1 (100%). Conclusion: the educational website was built, validated, and evaluated in a satisfactory manner. It can be considered an appropriate tool for its purpose, with benefits in the teaching-learning process for families regarding postnatal home care fornewborns through its use. It can also be used to educate students and health professionals. The website is available for free access via laptops, computers, smartphones, or tablets.